Significant promotion effect of Bi2O3on the activity and stability of directly assembled lanthanum manganite based cathodes of solid oxide fuel cells - Ai, N.; Veder, Jean-Pierre; Cheng, Y.; Chen, M.; Chen, K.; Zhang, T.; Jiang, S. (The Electrochemical Society, Inc, 2017)
© 2017 The Electrochemical Society. All rights reserved. Bismuth oxide exhibits extraordinary ionic conductivity and high surface exchange ability, but the low melting temperature and instability in reducing environment limits its wide application in intermediate temperature solid oxide fuel cells (IT-SOFCs). Herein, we incorporate yttria-stabilized bismuth oxide (YSB) as a promoter to enhance the electrocatalytic activity of directly assembled La 0.76 Sr 0.19 Mn 0.95 Pt 0.05 O 3+δ (LSMPt) cathodes on yttria-stabilized zirconia (YSZ) electrolyte. The presence of YSB enhances the electrocatalytic activity of LSMPt for the oxygen reduction reaction (ORR) with significantly reduced activation energy of 127 kJ mol −1 for ORR, as compared to 171 kJ mol −1 for the reaction on pristine LSMPt cathode. An anode-supported YSZ film cell with the directly assembled LSMPt-YSB electrode exhibits a peak power density of 1.36 and 0.35 W cm −2 at 750 and 600°C, respectively and is stable with no degradation during the operation for over 200 h. Synchrotron near edge X-ray absorption fine structure spectroscopy (NEXAFS) and energy dispersive spectroscopy (EDS) reveal that the excellent performance and stability is owing to in situ formation of ionic conducting Mn-Bi containing particles or phase at the electrode/electrolyte interface under the influence of electrochemical polarization. The present study opens up a new avenue to apply the active bismuth oxide for the development of highly active and durable cathodes of IT-SOFCs.